Incomplete conquests the limits of Spanish empire in the seventeenth-century Philippines - Mawson, Stephanie Joy 1984- (Ithaca Cornell University Press, 2023)
"This book tells a story of the limitations of empire, unearthing histories of resistance, flight, evasion, conflict, and warfare from across the breadth of the Philippine archipelago during the seventeenth century."-- Provided by publisher.
A moment of crisis: 1660-1663 -- Slavery, debt, and colonial labor regimes -- Contested conversions -- Slave rRaiding and imperial retreat -- Mountain refuges -- Cagayan insurgencies, 1572-1745 -- Manila: the Chinese City.
Includes bibliographical references and index.
Keywords: Indigenous peoples -- Philippines; Philippines -- History -- 1521-1812.; Philippines -- Colonization -- History -- 17th century; Spain -- Colonies -- Asia -- History -- 17th century